2018
DOI: 10.1021/acs.biomac.8b01468
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Nitrogen Mustard-Based Autofluorescent Amphiphilic Brush Copolymer as pH-Responsive Drug Delivery Vehicle

Abstract: Delivery of clinically approved nonfluorescent drugs is facing challenges because it is difficult to monitor the intracellular drug delivery without incorporating any integrated fluorescence moiety into the drug carrier. The present investigation reports the synthesis of a pH-responsive autofluorescent polymeric nanoscaffold for the administration of nonfluorescent aromatic nitrogen mustard chlorambucil (CBL) drug into the cancer cells. Copolymerization of poly­(ethylene glycol) (PEG) appended styrene and CBL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 61 publications
0
46
0
Order By: Relevance
“…MTT cytotoxicity assays were performed to evaluate the cytotoxicity of CD-based PRs. 39 As shown in Fig. 5A, HepG2 cells retained about 90% viability after incubation for 24 h in the presence of CD-based PRs below a concentration of 100 µg mL −1 , indicating that the three CD-based PRs had no significant cytotoxicity.…”
Section: Cytotoxicity and Protein Adsorption Of Cd-based Prsmentioning
confidence: 82%
“…MTT cytotoxicity assays were performed to evaluate the cytotoxicity of CD-based PRs. 39 As shown in Fig. 5A, HepG2 cells retained about 90% viability after incubation for 24 h in the presence of CD-based PRs below a concentration of 100 µg mL −1 , indicating that the three CD-based PRs had no significant cytotoxicity.…”
Section: Cytotoxicity and Protein Adsorption Of Cd-based Prsmentioning
confidence: 82%
“…pH stimuli helped in the effective apoptosis of cancer cells via this platform [ 7 ]. Saha et al reported on the development of a pH-triggered auto-fluorescent polymeric nanoplatform for the delivery of nonfluorescent aromatic nitrogen mustard chlorambucil (CBL) to cancer tumors [ 8 ]. pH variance is, therefore, a fundamental variable for the evolution of sophisticated DDSs.…”
Section: Types Of Stimulimentioning
confidence: 99%
“…Also, these polymers are biocompatible, less toxic, and easy to prepare than most other aggregation‐induced emission luminogens (AIEgens). Being empowered with these advantages, S‐MA alternating copolymer is used as novel stimuli‐responsive polymeric materials, [ 126,127 ] for sensing application, [ 128 ] for drug delivery, [ 129 ] etc.…”
Section: Nonconventional Luminogenic Property Of S‐mi/ma Copolymersmentioning
confidence: 99%
“…Amino acid‐derived PSMI‐based alternating polyampholyte was reported by Saha et al where both the comonomers were functionalized with leucine. [ 129 ] It was observed that the synthesized deprotected polymer becomes charge‐neutral at pH 7.0. Further, this polymeric material can selectively sense carbon disulfide (CS 2 ) in the aqueous and vapor phase (naked‐eye colorimetric detection) with great sensitivity.…”
Section: Nonconventional Luminogenic Property Of S‐mi/ma Copolymersmentioning
confidence: 99%